Patient Satisfaction on Restorative Procedure at Selected Private Dental Chambers in Dhaka City: Patient satisfaction on restorative procedure - Islam, Nabhira Aftabi Binte; Haque, Md Mahmudul; Barman, Neela (Journal of Preventive and Social Medicine, 2020)
Background: The simultaneous application of technical and artistic skills of restorative procedure enables a practitioner to achieve outstanding esthetic and functional results upon the patient’s satisfaction. Objectives: To assess patient satisfaction on restorative procedure at selected dentist chambers in Dhaka city. Materials and methods: It was a cross-sectional study which was conducted to estimate the patient satisfaction on restorative procedure at selected dental chambers in Dhaka city. The respondents were selected purposively. Data were collected through face to face interview and reviewing records with the help of a questionnaires and checklist respectively. Places and period of study: The study populations were conducted in dental chambers at Uttara in Dhaka city. Total 43 patients were interviewed purposively. Results: Majority of the respondents (44.2%) belonged to 20-30 years of age. Male and female were 49% and 51% in number. Educational qualification of the respondents included 4.7% S.S.C, 37.2% H.S.C, 58.1% were in Graduate. Among the respondents 37.2% were service holders, 41.9% were businessmen and 20.9% were nonemployee. 14% of all had monthly income was 30,000 tk, and 41.9% had monthly income was 31-50,000 tk. 28% respondents did G.I, 51.2% used Light cure filling materials and 20.9% with amalgam filling materials. 37.2% respondents were satisfied about restoration, 41.9% told very good about the quality of restoration and 30.2% satisfied about the color. Quality of restoration and perfection of the use on patient was significantly associated (p< .05). Conclusion: Due to the recent elevation of patient expectations regarding dental care, the education, training, and individual cultivation of dentists must be adjusted to ensure their satisfaction. JOPSOM 2019; 38(2): 63-67